Respiratory response to finger clamping in dogs under general anesthesia: A descriptive pilot study - Sylvain, Lepape; Jerneja, Sredensek; Karine, Portier (Frontiers in Veterinary Science, 2022)
Aim of the study: The aim of this study was to assess the effects of a nociceptive stimulus on respiratory variables in anesthetized dogs. Material and method Eleven dogs received acepromazine administered intramuscularly (IM) at a dose of 0.04 mg.kg-1 45 minutes before induction of anesthesia. Loss of consciousness was obtained with midazolam at 0.2 mg kg-1 and propofol administered at a dose of 2 mg kg-1 intravenously (IV). Orotracheal intubation was performed and anesthesia was maintained with isoflurane in 100% oxygen. Inspired (VTi) and expired (VTe) tidal volume (VT), minute volume (VM), inspiratory and expiratory time (Ti; Te) were measured and recorded twice a second by a spirometer. The Drive (VT/Ti) and Timing (Ti/ TT ) were calculated. After stabilizing the depth of anesthesia the variables measured by the spirometer were recorded for 5 minutes [T0-5-T0]. Then (T0) interdigital clamping of the hind leg was performed until a withdrawal movement was observed. If no reaction occurred, the clamp was left in place for 60s. After removal of the clamp, respiratory variables were measured continuously for another five minutes [T0-T0+5]. At T0+5 morphine (0.2 mg.kg-1 IV) was administered. Five minutes later (T0+10), a second clamp test was performed, using the same procedure. At T0+15 the data recording was stopped. Result The results showed a large variation in the individual values of Drive and Timing and are presented in a descriptive manner. The observation of Drive values over time showed variations following nociceptive stimuli. Drive appears to have increased only for those dogs that did not move during the stimulus, and were therefore pinched for a full 60 seconds. In contrast, the study of the Timing values revealed no difference between the data before and after nociceptive stimulation. Conclusion Drive remains a parameter that needs to be studied in depth to determine its sensitivity and precocity. It seems that Drive may be an interesting parameter to include in the monitoring of acute nociception.